Association between Personal Well-being, Functional Status, Anxiety, Depression, Social Support and Spiritual Experience of Older Adults living in nursing Homes in Slovakia - Sováriová Soósová, Mária (Magyar Gerontológia, 2022)
Satisfaction with life is one of the most important pillars of successful ageing. Assessing the cognitive aspect of subjective well-being (which can be related to life satisfaction) is considered a useful complementary indicator for monitoring and comparing quality of life across countries.